The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.langmuir.2c01609
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Nano/Biointerface for Cell and Organ-Selective Drug Delivery

Abstract: The field of nanomedicine has rapidly grown in the past decades. Although a few nanomedicines are available in the market for clinical use, it is still challenging to develop nanomedicine targeting tissues beyond the liver. It has been recognized that even though the nanoparticles are modified with targeting ligands, the formation of a protein corona on the surface of nanoparticles in the biological fluids results in limited progress in nanoparticle-based drug delivery to specific cells or tissues. In this Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…To date, the influences of intrinsic properties of nanoparticles for protein corona formation have been extensively studied both in vitro and in vivo . , It has been illustrated that the intrinsic properties of nanoparticles (e.g., size, shape, surface charge, surface chemistry, and mechanical properties) play an important role in protein corona formation (Figure ). ,, Poly­(ethylene glycol) (PEG) is one of the ligands frequently used to reduce protein adsorption and confer a stealth property to avoid capture from the immune system. However, anti-PEG bodies were found as the product as a consequence of increased dosage of PEG-modified nanoparticles .…”
Section: Features Of the In Vivo Protein Corona Formation Of Nanopart...mentioning
confidence: 99%
“…To date, the influences of intrinsic properties of nanoparticles for protein corona formation have been extensively studied both in vitro and in vivo . , It has been illustrated that the intrinsic properties of nanoparticles (e.g., size, shape, surface charge, surface chemistry, and mechanical properties) play an important role in protein corona formation (Figure ). ,, Poly­(ethylene glycol) (PEG) is one of the ligands frequently used to reduce protein adsorption and confer a stealth property to avoid capture from the immune system. However, anti-PEG bodies were found as the product as a consequence of increased dosage of PEG-modified nanoparticles .…”
Section: Features Of the In Vivo Protein Corona Formation Of Nanopart...mentioning
confidence: 99%
“…10c). 131 The organ selective properties of O-LNPs and N-LNPs illustrated that after replacing the oxygen atoms with nitrogen atoms, the components of the protein corona adsorbed on the surface of LNPs will change greatly. Although the highest content of the protein is albumin, the second and third highest proteins will change from ApoE and complement C1 (O-LNPs) to fibrinogen beta chain and fibrinogen gamma chain (N-LNPs), leading to a change from liver-targeting to lung-targeting.…”
Section: Protein Corona-based Mechanismsmentioning
confidence: 99%
“…However, recent studies revealed that N-series LNP, whose lipid tails contain amide bonds, are capable of selectively delivering mRNA to the lung while O-series LNP with ester bonds in the tails result in the delivery of mRNA to the liver. [93,298,299] These integrative strategies of combining LNP and functional modification have led to the successful delivery of long mRNA-loaded LNP (e.g., human factor VIII (hFVIII) (≈4.5 kb)) to various organs. Zhang et al demonstrated that functionalized N 1 ,N 3 ,N 5 -tris(2aminoethyl)benzene-1,3,5-tricarboxamide derivatives (FTT) promotes in vivo mRNA delivery due to high biodegradability as well as base editing of mRNA gene.…”
Section: Selective Organ Targetingmentioning
confidence: 99%